Apology–forgiveness cycle in restorative justice, but how? - Suzuki, Masahiro (International review of victimology, 2023)
The apology–forgiveness cycle is a simple but powerful process for conflict resolution. Given the prevalence of apology and forgiveness in restorative justice (RJ), the apology–forgiveness cycle may take place. However, there is a lack of theoretical understanding of the relationship between apology and forgiveness in the RJ processes. After identifying key elements and impediments of the apology–forgiveness cycle during RJ meetings based on the existing literature, we develop a theoretical model of the apology–forgiveness cycle during RJ encounters. This typology explains how the apology–forgiveness cycle is intertwined with the RJ process, subsequently facilitating, blocking, and changing its sequence. There are four cycles: (1) apology facilitating forgiveness, (2) apology without forgiveness, (3) forgiveness promoting apology, and (4) forgiveness without apology. We conclude by offering future directions for research on the apology–forgiveness cycle in RJ.